Narrative Review: Physical Environmental , Sociodemographic, and Biological Factors on Dengue Fever in Children Aged 0-15 Years - Rusna Azizah Aziz; Blego Sedionoto; Akhmad Azmiardi (Faculty of Public Health Mulawarman University, Indonesia, 2025)
Objective : This review aims to synthesize evidence narratively regarding the relationship between physical environmental , sociodemographic, and biological factors and the incidence of dengue fever in children aged 0-<15 years. Research Methods/ Implementation Methods : This narrative review was conducted by searching articles in the PubMed and Google Scholar databases from 2016 to 2025. The main keywords used included